A new species of Paratagalis Monte from Brazil with taxonomical notes and a key to New World genera of Saicinae (Hemiptera: Heteroptera: Reduviidae: Saicinae) - Gil-Santana, Hélcio R.; Costa, Luiz A. A. (Zootaxa, 2009)
Paratagalis zikani sp. nov. from Brazil is described. A revised diagnosis of Paratagalis Monte, 1943, is provided. Morphological variation and sexual dimorphism of Paratagalis spinosus Monte, 1943, are described for the first time. A key to the Saicinae genera of the New World is provided.